Long-term Efficacy and Safety of Liquid AbobotulinumtoxinA Formulation for Moderate-to-Severe Glabellar Lines: A Phase III, Double-Blind, Randomized, Placebo-Controlled and Open-Label Study. (2nd September 2021) - Kestemont, Philippe; Hilton, Said; Andriopoulos, Bill; Prygova, Inna; Thompson, Catherine; Volteau, Magali; Ascher, Benjamin
Abstract: Background: A ready-to-use liquid formulation of abobotulinumtoxinA (aboBoNT-A solution) has been developed. Objectives: The aim of this study was to assess the long-term efficacy and safety of aboBoNT-A solution for the treatment of glabellar lines. Methods: This was a multicenter, multinational, Phase III study (NCT02493946), with randomized double-blind placebo-controlled (DBPC; 2:1 aboBoNT-A solution 50 U/placebo) and open-label (4 cycles aboBoNT-A solution) periods; additional patients were recruited into the open-label period. Patients were 18 to 65 years old, BoNT-naïve, and dissatisfied/very dissatisfied with moderate/severe glabellar lines at maximum frown. Investigator's live assessment (primary endpoint)/subject's self-assessment of glabellar line severity at maximum frown, patient satisfaction with glabellar line appearance, and FACE-Q patient-reported scales (facial appearance overall, psychological well-being, aging) were assessed. Adverse events were monitored. Analyses were performed on DBPC and long-term analysis (LTA; all patients receiving ≥1 aboBoNT-A solution injection) populations. Results: Responder rates for the investigator's live assessment, the subject's self-assessment, and patient satisfaction were consistent at Day 29 postinjection across repeat LTA cycles (82.2%-87.8%, 62.8%-80.6%, and 72.2%-87.8%, respectively), with statistically significantly higher responder rates vs placebo (DBPC cycle: 81.6% vs 0.8%, 68.1% vs 2.3%, and 83.1% vs 5.7%, respectively; all P < 0.0001). Consistent improvements on FACE-Q scales occurred with repeat cycles (DBPC cycle: aboBoNT-A solution vs placebo, P < 0.0001). No new or unexpected adverse events, or neutralizing antibodies, were observed. Conclusions: These results support the long-term efficacy and safety of aboBoNT-A solution, and its superiority over placebo, for treatment of glabellar lines in adults. Level of Evidence: 1: